Կաթողիկոսական պատկերների և ծիսական հանդերձանքի պատկերագրությունը 13-16-րդ դդ. հայ միջնադարյան գրքարվեստում - Սոֆի Խաչմանյան (ՀՀ ԳԱԱ հրատ.)
В искусстве книжного дела средневековой Армении изображение католикосов под аркой, на фоне архитектурных сооружений или на деталях этих сооружений была традицией канонической иконографии. Изображение католикоса со всеми ритуальными одеяниями также каноническая традиция - они были изображены в определенных сценах или позах. Многообразие рисунков и изображенных на них ритуальных одеяний объясняется географической территорией их создания и многообразием творческих направлений школ миниатюры средневековой Армении. Depicting the Catholicos beneath the arch/altar and on the background of architectural structures or elements, was a canonical iconographic tradition in the Medieval Armenian miniature painting. The presentation of the Catholicos with a complete ritual outfit was also a tradition where they were illustrated in certain scenes or in certain positions. The presence of iconographic diversity of paintings and ritual clothing portrayed in them, is explained by the diversity of the geographical area of the art production and the creative directions of various miniature schools that existed in Medieval Armenia.
Keywords: Christianity; Fine Arts; Illuminating of Manuscripts and Books; Mural Painting